2021
DOI: 10.1111/jnu.12738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of massage therapy with lavender oil on severity of restless legs syndrome and quality of life in hemodialysis patients

Abstract: This study assessed the effects of massage therapy using 5% lavender oil on the severity of restless legs syndrome (RLS) and the quality of life (QoL) of patients on hemodialysis (HD). Design and methods:This is a randomized placebo-controlled study with a pretestposttest design. This study was conducted from January 30, 2019, to May 6, 2019, at HD centers in Turkey, and it includes 58 participants-31 study patients and 27 controls. Data were collected using patient identification form, RLS severity rating sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
0
11
0
2
Order By: Relevance
“…No blinding was performed in the remaining six studies [7, 17, 19, 21, 25, 27]. Regarding withdrawals and dropouts, eight studies were of strong quality [18, 20–24, 26, 28], while five studies were of low quality due to high rates of withdrawals and dropouts or lack of reporting [7, 16, 17, 19, 27] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No blinding was performed in the remaining six studies [7, 17, 19, 21, 25, 27]. Regarding withdrawals and dropouts, eight studies were of strong quality [18, 20–24, 26, 28], while five studies were of low quality due to high rates of withdrawals and dropouts or lack of reporting [7, 16, 17, 19, 27] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review and meta‐analysis is the first to present results from 14 studies that investigated the effects of non‐pharmacological methods on cramping and RLS in HD patients during the past 20 years. The findings of those studies indicated that muscle‐related problems were frequently observed in HD patients [17–20, 22, 23, 26]. Caplin et al (2011) emphasized that cramping was a common complication associated with HD, with a rate of 74% [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 HBS olan hastalarda, TİT yöntemlerinin kullanımına yönelik yapılan çalışmalar incelendiğinde, HBS belirtilerinin yönetiminde aromaterapi, masaj, egzersiz, yoga, refleksoloji, akupunktur, sıcak ve soğuk uygulama, doğal ürünler ve transkütanöz elektriksel sinir stimülasyonu [transcutaneous electrical nerve stimulation (TENS)] gibi yöntemlerin hastalarda olumlu etkilerinin olduğu görülmüştür. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]…”
Section: Klinik Anlamlılık Ile Ilişkili Belirteçlerunclassified
“…50 Hemodiyaliz (HD) tedavisi alan bireylerde haftada 3 kez, 4 hafta boyunca, her 2 alt bacağa 10 dk (toplam 20 dk) lavanta yağı (%5) ile müdahale grubuna uygulanan masajın, plasebo kontrol grubuna göre HBS şiddetini azalttığı ve yaşam kalitesini artırdığı belirlenmiştir. 23 HD tedavisi alan hastalarda gliserin ve lavanta yağı ile yapılan masajın, HBS şiddeti üzerine etkisini belirlemek amacıyla yapılan bir başka çalışmada ise müdahale gruplarına 4 hafta boyunca haftada 3 kez 10-15 mL gliserin (%2) ve lavanta yağı (%1,5) ile 45 dk basit öfloraj masajı uygulanmış, kontrol grubuna ise rutin bakım verilmiştir. Gliserin ve lavanta yağıyla yapılan masajın, müdahale grubunda kontrol grubuna göre HBS şiddetini azalttığı, ancak her iki müdahale grubu arasında HBS şiddetinde azalmada anlamlı bir farklılık olmadığı tespit edilmiştir.…”
Section: Huzursuz Bacak Sendromu Yöneti̇mi̇nde Sik Kullanilan Tamamla...unclassified